"Side by side": Comparing how Israeli secular and religious mothers read a story about the Israeli‐Palestinian conflict to young children. Issue 4 (13th May 2022) - Smadja, Marie‐Lyne; Aram, Dorit; Agmon, Naama; Ziv, Margalit; Bar‐Tal, Daniel
Abstract: The Israeli‐Palestinian conflict has deleterious effects on children. Our research observed mothers' conversations with their 5‐7‐year‐old children about the conflict during shared book reading (SBR) of a fiction book, indirectly depicting the conflict. Using a mixed‐methods study, we compared the SBR of secular and religious Israeli Jewish mothers. We videotaped the SBR interactions and interviewed the mothers about the nature of their SBR conversations with their child and their perceptions of political socialization of children. The main findings showed that despite their tendency to perceive the conflict differently, secular and religious mothers shared the book similarly. Most of them preferred to talk about the conflict as little as possible with their child but appreciated the opportunity that the book provided them to discuss it in an age appropriate manner. Our discussion focuses on the potential of SBR to assist parents in explaining the conflict to young children.